The ultimate question? Evaluating the use of Net Promoter Score in healthcare: A systematic review - Corey Adams; Ramesh Walpola; Anthony M. Schembri; Reema Harrison (Wiley, 2022)
Abstract Background Patient experience is a complex phenomenon that presents challenges for appropriate and effective measurement. With the lack of a standardized measurement approach, efforts have been made to simplify the evaluation and reporting of patient experience by using single‐item measures, such as the Net Promoter Score (NPS). Although NPS is widely used in many countries, there has been little research to validate its effectiveness and value in the healthcare setting. The aim of this study was to systematically evaluate the evidence that is available about the application of NPS in healthcare settings. Methods Studies were identified using words and synonyms that relate to NPS, which was applied to five electronic databases: Medline, CINAHL, Proquest, Business Journal Premium, and Scopus. Titles and abstracts between January 2005 and September 2020 were screened for relevance, with the inclusion of quantitative and qualitative studies in the healthcare setting that evaluated the use of NPS to measure patient experience. Results Twelve studies met the inclusion criteria. Four studies identified benefits associated with using NPS, such as ease of use, high completion rates and being well‐understood by a range of patients. Three studies questioned the usefulness of the NPS recommendation question in healthcare settings, particularly when respondents are unable to select their service provider. The free‐text comments section, which provides additional detail and contextual cues, was viewed positively by patients and staff in 4 of 12 studies. According to these studies, NPS can be influenced by a wide range of variables, such as age, condition/disease, intervention and cultural variation; therefore, caution should be taken when using NPS for comparisons. Four studies concluded that NPS adds minimal value to healthcare improvement. Conclusion The literature suggests that many of the proposed benefits of using NPS are not supported by research. NPS may not be sufficient as a stand‐alone metric and may be better used in conjunction with a larger survey. NPS may be more suited for use in certain healthcare settings, for example, where patients have a choice of provider. Staff attitudes towards the use of NPS for patient surveying are mixed. More research is needed to validate the use of NPS as a primary metric of patient experience. Patient or Public Contribution Consumer representatives were provided with the research findings and their feedback was sought about the study. Consumers commented that they found the results to be useful and felt that this study highlighted important considerations when NPS data is used to evaluate patient experience.